Boost Public Service Productivity with Effective IT Governance - Juliyandri Saragih; Darmeli Nasution (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Consumer demand for fast, accurate, and precise information has accelerated the adoption of information technology (IT) as a strategic tool in this era of globalization. The implementation of IT governance in public services plays an important role in improving efficiency, productivity, and service quality, by meeting community needs effectively. This study aims to evaluate IT governance in the public service sector through the implementation of international standards such as COBIT, ITIL, and ISO/IEC 20000 which focus on risk management, information security, and service efficiency. This research method uses a qualitative approach by analyzing related frameworks and regulations, and identifying factors that support and hinder effective IT governance. The results of the study indicate that the implementation of IT governance in public services faces significant challenges, including resistance to change, limited resources, and lack of readiness to adapt to changes in community values. The success of IT governance depends on the synergy between organizational policies, information strategies, and information architecture standards applied. In addition, the ITIL-based service model that emphasizes the integration of People, Process, Products, and Partners (4P) components has proven effective in improving the quality and satisfaction of public service users. This study recommends increasing inter-agency collaboration, improving technology infrastructure, and increasing digital literacy to ensure responsive, accountable, and sustainable IT governance in the public service sector.